HAMBATAN-HAMBATAN SISWA DALAM MENGIKUTI KOMPETENSI PEMBUATAN BUSANA WANITA KELAS XI DI SMK N 1 IV ANGKEK KABUPATEN AGAM - Rahmayuni, Pepi; Katin, Yusmar Emmy; Idrus, Yenni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
This study aims to determine the barriers to student learning in the following competencies manufacture ladies fashion class XI in SMK N 1 IV Angkek Agam District in particular the manufacture of working clothes. Includes several indicators which measure decision ways, making basic patterns, making the burst pattern in accordance with the design, material cutting and marking patterns and sewing techniques. This type of research is descriptive quantitative. Techniques for data collection in this study uses total sampling with 24 people of sample. Type of instrument is used in the form of questionnaires. The results showed students in vocational SMK N 1 IV Angkek Kab. Agam experiencing barriers to learning, namely (1) take a measurement with high category, (2) create a basic pattern with a high enough category, (3) create a burst pattern according to the category of high design, (4) put the pattern and cut the material by category high (5) sewing techniques with high category. Barriers average student in the following competencies in manufacturing women's clothing considered quite.